Preserving local research articles to create visibility and knowledge sharing among researchers and students worldwide: University of Malaya institutional repository - Ranita, H.S.; Mohd Faizal, H. (2011)
Now, more than ever, the way information is stored, retrieved and displayed is changing. Simple bibliographic databases are giving way to unregulated and unorganized multimedia data repositories, which can give the user great difficulty when searching for information. The concept of selectivity in preserving electronic records is very important. The user does not want to be given lots of useless information. In this discussion, it can be seen that the international collaborations have produced a standard describing the functions of a trusted digital repository and the characteristics of one that can be trusted. These discussions provide an abstract frame of reference for evaluating such repositories, but meaningful evaluation requires that they be supplemented by empirical data on the purpose of each repository and the institutional, cultural and resource context in which it operates. Informed evaluation will consider how a repository balances the competing objectives of preservation and dissemination, whether it is defined primarily in terms of a community of producers or a community or users, and the extent to which it operates. In that sense of preserving the electronic records in a way of an open access which is the trusted digital repository. It will also reveal one of the electronic archive which is the E-print would be introduced and University of Malaya Library will be the source of an example. Access to electronic records is dependent on the constantly changing and evolving computer technology. Unlike paper records that can survive for hundreds of years unless measures are taken to destroy them, electronic records do not persist unless deliberate steps are taken to preserve them. The importance of preserving the electronic records will be clarified by implementing the trusted digital repository.